Intelligent Transport Systems 5th EAI International Conference, INTSYS 2021, Virtual Event, November 24-26, 2021, Proceedings - Martins, A.; Ferreira, J. (2022)
his book constitutes the proceedings of the 5th International Conference on Intelligent Transport Systems, INTSYS 2021, which was held in November 2021. Due to COVID-19 pandemic the conference was held virtually. With the globalization of trade and transportation and the consequent multi-modal solutions used, additional challenges are faced by organizations and countries. Intelligent Transport Systems make transport safer, more efficient, and more sustainable by applying information and communication technologies to all transportation modes. The 15 revised full papers in this book were selected from 31 submissions and are organized in three thematic sessions on mobility; blockchain and disaster management; and data analytics.